Empirical essays in international macroeconomics - McQuade, Peter Edward (Trinity College (Dublin, Ireland). Department of Economics, 2011)
This thesis is composed of three essays. The first paper examines private credit growth in Europe between 1999 and 2007. The results highlight the importance of external liabilities in facilitating the credit boom. Although private sector credit growth is correlated with the current account balance, some countries had rapid credit growth without large current account imbalances. We show that this because debt flows have a different relation to private credit growth than equity fiows. In addition, bank debt flows are more closely correlated with private credit growth than other debt flows. Finally, we find limited evidence that bank regulation and competition were important determinants of private credit growth during the period.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.